Factor analysis of the Brain Check Survey - Pickle, Sarah, author; Sample, Pat, advisor; Greene, David, advisor; Daunhauer, Lisa, committee member (Colorado State University. Libraries, 2013)
Children who have a traumatic brain injury (TBI) are under-identified and lack appropriate educational supports to help them achieve their academic goals. Because TBI can greatly impact a child's ability to succeed at school, there is a need for a convenient and effective way to screen for TBI in students who are struggling in school so they can obtain appropriate school-based services. The purpose of this study was to work toward establishing construct validity for the Brain Check Survey (BCS), which is a parent-report questionnaire intended to help school personnel screen for possible TBI in students. The BCS can act as a starting point in the process of qualifying students for Special Education, a 504 Plan, or Response to Intervention assistance. In five different school districts in Colorado, parents completed the BCS for their child who was recruited from one of three groups: has identified TBI, is currently receiving special education services for diagnosed specific learning disabilities, or is considered typically developing. Construct validity was tested using multiple factor analyses: 1) all participants combined (typically developing, traumatic brain injury, and specific learning disability), 2) elementary, middle, and high school level categories of all participants, and 3) all ages from the typically developing group only. These factor analyses confirmed the two-factor construct of the BCS that measures student Symptoms and Behaviors. The analysis also gave insight into two distinct aspects of behaviors that the instrument is measuring: Cognitive Processing and Behavior Control. The positive findings from this factor analysis study suggest that the BCS has strong construct validity and can be effective in screening students for possible TBI.
Keywords: screening; validity; traumatic brain injury; children; occupational therapy; special education